Apologija za krajevno knjižnico - Novljan, Silva (Knjižnica, 2013)
Purpose: The purpose of the article is to strengthen the importance of a local library and its role in offering equal access to library services even to inhabitants of the smallest local communities. Methodology: Fulfilling the mission of a public library, a local library exercises equal human rights and fundamental freedoms for inhabitants of a local community. The research indicates that inhabitants of a small community having no local library are deprived of human rights and fundamental freedoms. The questionnaire was completed by central public libraries responsible for the accessibility of library services in their region. The research is based on the analysis of publicly available statistical data and responses to a questionnaire on library services in communities with no local library. The results place a public library among institutions behaving in a socially responsible way thus developing a democratic and responsible society. Results: The results confirmed that small communities having no local libraries are deprived of library services although they, together with the Ministry of Culture, co-finance a local library in a neighbouring community and have access to its services. Research limitations: The research is focused on verifying the accessibility of library services on a selected sample of communities and does not assess the entire scope and quality of public libraries' activity in realising common recommendations on the accessibility of public library services. Originality/practical implications: Testing the accessibility of library services on a selected sample of communities and the effect of solidarity on equal access to library services encourage the consideration of suitability of regulations on local library organisation, the attitude of the state, communities and central public libraries in preserving and developing a local library.
Keywords: public libraries; splošne knjižnice; človekove pravice; human rights; solidarity; solidarnost; public place; javni prostor; občine; communities